Notes on 5th instar nymphs of two species of Phaenacantha Horváth (Heteroptera: Colobathristidae) - Xue, Huai-jun; Bu, Wen-jun (Entomologica Fennica, 2005)
Fifth-instar nymphs of two species of colobathristid genus Phaenacantha from China are described, and the diagnosis of nymphal Colobathristidae and its significance in phylogenetic study are discussed.